Repurposing development genes for axonal regeneration following injury: Examining the roles of Wnt signaling - Albano, Gabrielle A.; Hackam, Abigail S. (Frontiers in Cell and Developmental Biology, 2024)
In this review, we explore the connections between developmental embryology and axonal regeneration. Genes that regulate embryogenesis and central nervous system (CNS) development are discussed for their therapeutic potential to induce axonal and cellular regeneration in adult tissues after neuronal injury. Despite substantial differences in the tissue environment in the developing CNS compared with the injured CNS, recent studies have identified multiple molecular pathways that promote axonal growth in both scenarios. We describe various molecular cues and signaling pathways involved in neural development, with an emphasis on the versatile Wnt signaling pathway. We discuss the capacity of developmental factors to initiate axonal regrowth in adult neural tissue within the challenging environment of the injured CNS. Our discussion explores the roles of Wnt signaling and also examines the potential of other embryonic genes including Pax, BMP, Ephrin, SOX, CNTF, PTEN, mTOR and STAT3 to contribute to axonal regeneration in various CNS injury model systems, including spinal cord and optic crush injuries in mice, Xenopus and zebrafish. Additionally, we describe potential contributions of Müller glia redifferentiation to neuronal regeneration after injury. Therefore, this review provides a comprehensive summary of the state of the field, and highlights promising research directions for the potential therapeutic applications of specific embryologic molecular pathways in axonal regeneration in adults.